2021
DOI: 10.3847/1538-3881/abd802
|View full text |Cite
|
Sign up to set email alerts
|

Host Star Metallicity of Directly Imaged Wide-orbit Planets: Implications for Planet Formation

Abstract: Directly imaged planets (DIPs) are self-luminous companions of pre-main-sequence and young main-sequence stars. They reside in wider orbits (∼tens to thousands of astronomical units) and generally are more massive compared to the close-in (≲10 au) planets. Determining the host star properties of these outstretched planetary systems is important to understand and discern various planet formation and evolution scenarios. We present the stellar parameters and metallicity ([Fe/H]) for a subsample of 18 stars known… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 159 publications
2
20
0
Order By: Relevance
“…from a single population. This reinforces the previous observations that the average metallicity of the host star decreases as the mass of the planet increases (Santos et al 2017;Narang et al 2018;Swastik et al 2021). A possible interpretation is that the population of giant planets is bimodal, with giant planets (M p ≤ 4 M J ) forming via core accretion and more massive giant planets (M p > 4 M J ) forming via the disk gravitational instability.…”
Section: Discussionsupporting
confidence: 89%
“…from a single population. This reinforces the previous observations that the average metallicity of the host star decreases as the mass of the planet increases (Santos et al 2017;Narang et al 2018;Swastik et al 2021). A possible interpretation is that the population of giant planets is bimodal, with giant planets (M p ≤ 4 M J ) forming via core accretion and more massive giant planets (M p > 4 M J ) forming via the disk gravitational instability.…”
Section: Discussionsupporting
confidence: 89%
“…Figure 7 shows the cumulative metallicity distribution for host stars of these two samples, which a Kolmogorov-Smirnov (K-S) test 5 shows has a very low p-value of 9.53 ×10 −8 to be drawn from a single population. This reinforces the previous observations that the average metallicity of the host star decreases as the mass of the planet increases (Santos et al 2017;Narang et al 2018;Swastik et al 2021). A possible interpretation is that the population of giant planets is bimodal, with giant planets (m p ≤ 4 M J ) forming via core accretion and more massive giant planets (m p > 4 M J ) forming via the disk gravitational instability.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, several studies have pointed out the existence of correlations between characteristics of the host stars and properties/frequencies of their planetary systems, in particular for giant transiting planets, for which the present work is focused on. As a result, the evidences supporting the correlation between stellar metallicity and occurrence rate of giant planets (e.g., Santos et al 2004;Valenti et al 2005) and the weakening of this correlation towards lower regimes of planetary mass (e.g., Sousa et al 2008;Ghezzi et al 2010) or for wide-orbit planets (Swastik et al 2021), the connection between planet radius and stellar metallicity (Buchhave et al 2014), the correlation between stellar metallicity and planetary heavy-metal content (e.g., Guillot et al 2006), the trend between orbit eccentricity and star metallicity (Dawson & Murray-Clay 2013), the role of the abundances of α-elements (Robinson et al 2006;Gonzalez 2009;Adibekyan et al 2012cAdibekyan et al , 2015 or of the Li depletion observed for massive planet-hosting stars (e.g., Delgado are becoming more and more numerous thanks to the constant increase of new planet discoveries.…”
Section: Introductionmentioning
confidence: 75%